Narragunnawali: Reconciliation in Education - Nicholas, Biddle (My University, 2022)
The aim of this paper is to track and analyse engagement with Reconciliation Australia’s Narragunnawali: Reconciliation in Education program, and the relationship this engagement has with a range of observed outcomes. We draw on multiple sources of data – administrative data collected as part of the operation of the program, and the Longitudinal Study of Indigenous Children. We find very strong evidence that those schools and Aboriginal and Torres Strait Islander students that engage with Narragunnawali have improved outcomes, from the perspective of reconciliation in education.
Capturing the impact of Narragunnawali
Keywords: Government, law and policy